2020
DOI: 10.3390/mps3030053
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly High Levels of Inverted Re-Insertions Using Paired sgRNAs for Genomic Deletions

Abstract: Use of dual sgRNAs is a common CRISPR/Cas9-based strategy for the creation of genetic deletions. The ease of screening combined with a rather high rate of success makes this approach a reliable genome engineering procedure. Recently, a number of studies using CRISPR/Cas9 have revealed unwanted large-scale rearrangements, duplications, inversions or larger-than-expected deletions. Strict quality control measures are required to validate the model system, and this crucially depends on knowing which potential exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Mutations were verified by Sanger-sequencing of the subcloned amplicons, and absence of the respective protein was confirmed by immunoblotting. Of note, we obtained several clones in which the excised exon was found inverted and re-inserted, nevertheless giving a full KO phenotype as described (Blayney et al, 2020). All clones selected for this study were confirmed homozygous deletions.…”
Section: Methodsmentioning
confidence: 98%
“…Mutations were verified by Sanger-sequencing of the subcloned amplicons, and absence of the respective protein was confirmed by immunoblotting. Of note, we obtained several clones in which the excised exon was found inverted and re-inserted, nevertheless giving a full KO phenotype as described (Blayney et al, 2020). All clones selected for this study were confirmed homozygous deletions.…”
Section: Methodsmentioning
confidence: 98%
“…Cells were reprogrammed by exogenous expression of OCT3/4, SOX2, cMYC and KLF4 using a Sendai virus vector (41). To generate exon 2 -/-iPSCs (A4 and D1 clones), a dual single guide RNA (sgRNA) approach was chosen to recruit Cas9-2NLS (Synthego) to cut within intron 1 and 2 to remove CLU exon 2 (Additional le 1, table S1) (42). Transfection of CTR iPSCs was performed using Nucleofection and an optimised protocol (Synthego).…”
Section: Methodsmentioning
confidence: 99%
“…The CTR iPSCs were previously generated from the Price lab at King's College London from human keratinocytes obtained from a healthy, neurotypical adult male, as previously described [45][46][47] . CTR iPSCs were used to generate exon 2 −/− iPSCs (A4 and D1 clones), a dual single guide RNA (sgRNA) approach was chosen to recruit Cas9-2NLS (Synthego) to cut within intron 1 and 2 to remove CLU exon 2 (Supplementary Table 1) 48 . Transfection of CTR iPSCs was performed using Nucleofection and an optimised protocol (Synthego).…”
Section: Methodsmentioning
confidence: 99%